Role of social workers in mitigating the effects of climate change in Makonde communal lands, Zimbabwe - Nyahunda, Louis; Matlakala, Frans Koketso; Makhubele, Jabulani Calvin (Penerbit Universiti Kebangsaan Malaysia, 2019)
Climate change is among the most vital environmental aspects that the human community is endowed with. Climate as a factor of life is particularly strong to low income rural communities whose livelihoods heavily depend on rain-fed subsistence agriculture like Makonde communal lands. The purpose of social work within the context of climate change is to enhance community expertise and empower members for participation in the decision-making process through all stages of risk assessment, rescue, planning and intervention for recovery and preparedness. This paper sought to explore the role of social workers in mitigating the effects of climate change in Makonde communal lands of Zimbabwe. The objectives of the study were to identify what roles if any are social workers playing in mitigating the effects of climate change and if not, what are the impediments in that sphere. A qualitative research approach was followed within the traditional framework of descriptive and exploratory designs. Simple random, purposive and snowballing sampling techniques were used to gather twenty-five participants in the study. The Thematic Content Analysis was followed to analyse data inductively. The study found that Social Workers are not directly involved in climate change interventions in the Makonde area owing it to lack of training on climate change issues. The study recommends that climate change falls within the purview of the social work practice therefore social workers must take the lead in supporting families and communities affected by climate change following the values, knowledge base, skills and principles of the profession.